PCL/chitosan composite films enhanced with Bi2O3 in nuclear shielding applications: Irradiation resistance, thermal and structural properties - Yilmaz, Demet; Pekdemir, Mustafa Ersin; Dik, Gamze; Pekdemir, Sibel Selcuk; Ulu, Ahmet; Tasgin, Yahya; Ates, Burhan (Wiley, 2025)
In this work, irradiation resistance, thermal, and structural characteristics of Bi2O3-reinforced poly epsilon-caprolactone/chitosan composites for nuclear shielding applications were studied. PCL/CTS/Bi2O3 composite films were prepared by using different amounts of Bi2O3 (0.5%-4.0% (w/v)). The radiation shielding parameters of the synthesized composite films were both experimentally and theoretically measured at the high energy region. The equivalent dose rates of the prepared film samples were measured using a fast neutron source. Also, to determine the irradiation resistance, the samples were irradiated with Am-241 and Co-60 sources for 30 days. The MFP values at 80.99 keV changed by approximately 61% in samples PCL/CTS and PCL/CTS/4% Bi2O3. The results show that Bi2O3 content increases the gamma shielding abilities in PCL/CTS films. According to TGA results, the thermal stability of the polymer composite films is increased by the addition of Bi2O3 to the PCL/CTS blend film. The results show that PCL/CTS composite materials can be used as protective coating materials for nuclear shielding.Highlights PCL/CTS/Bi2O3 composite films were prepared by the solvent casting method. The thermal stability of the composite films increased by increasing the Bi2O3 amount. Bi2O3 increased the LAC and MAC values of the composite films. PCL/CTS/Bi2O3 composite films have a neutron shielding effect.
Keywords: bismuth oxide; chitosan; composite; poly epsilon-caprolactone; radiation shielding